Enriching student soft skills through compulsory university courses based on blended learning T&L - Alagappar, Ponmalar N.; Che Husain, Faridah; Mat Noor, Noor Ain (2017)
This study focuses on enrichment of soft skills elements embedded in compulsory university course through blended learning. In this context, emphasis is given to three compulsory university courses, namely Ethnic Relations, Islamic and Asian Civilization (TITAS), as well as Entrepreneurship Culture. A pilot study through distribution of survey questionnaires and a case study were conducted amongst students enrolled in Basic Entrepreneurship Culture (GIG 1003) and Ethnic Relations (GIG 1002) to test reliability and validity of the instrument. It also aimed to measure early stage of soft skills embedment amongst students. The questionnaire contains 3 parts, namely communication skills (13 items), critical thinking and problem solving (12 items), as well as team work skills (13 items). Evaluation was based on 5-point likert scale, beginning with the lowest scale (1) and ending with highest scale (5). A total of 350 questionnaire forms were distributed to several teaching groups from the Ethnic Relations course. From the total, only 232 forms were accepted and analysed for the pilot survey. This number was regarded adequate to test reliability and validity of the instrument. Data analysis was carried out using Statistical Package for Social Science (SPSS) version 22. The reliability of the questionnaire was measured using the Cronbach's alpha coefficient. The findings based on Cronbach's alpha showed that all variables exceeded 0.70 as recommended by Nunnally (1978). Exploratory factor analysis was used to determine the validity of the construct. To examine the basic structure of the questionnaire which comprised of 38 items, the data collected were analysed using principle axis factoring with varimax rotation. Therefore, the findings of the study showed that the validity and reliability of the questionnaire was very suitable to be used to measure the level of soft skills amongst the students.